2011
DOI: 10.4155/bio.11.204
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Punches for Confirmation of Suspected γ-Hydroxybutyric Acid Intoxications: Validation of an Optimized GC–MS Procedure

Abstract: A sensitive GC-MS method for GHB analysis in DBS was successfully optimized and validated. The successful analysis of DBS collected from GHB abusers suggests the routine applicability of the DBS sampling technique for GHB analysis in toxicological cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Hct and blood volume had a considerable impact on the concentrations of caffeine and paraxanthine, similar to that described for several other small molecules [32][33][34][35]. The range in which the impact of Hct was evaluated, 0.20 -0.60, was considered to be relevant and sufficient, as it covers approximately 99.5% of a hospital population (including both 'normal' and 'critically ill' patients) [10].…”
Section: Discussionmentioning
confidence: 92%
“…Hct and blood volume had a considerable impact on the concentrations of caffeine and paraxanthine, similar to that described for several other small molecules [32][33][34][35]. The range in which the impact of Hct was evaluated, 0.20 -0.60, was considered to be relevant and sufficient, as it covers approximately 99.5% of a hospital population (including both 'normal' and 'critically ill' patients) [10].…”
Section: Discussionmentioning
confidence: 92%
“…Based on that study, it can be concluded that DBS from capillary blood can be used as a suitable alternative for venous blood. [7] 3 Results…”
Section: Dbs Analysismentioning
confidence: 99%
“…One µL of the derivatized extract was injected into the GC-MS, operating in selective ion monitoring (SIM) mode for quantification. [7] The method used has a lower and upper limit of quantification of 2 and 100 µg/mL GHB, respectively. Of those DBS with a GHB concentration above 100 µg/mL, the final ethylacetate extracts were diluted ten-fold according to the previously validated dilution technique.…”
Section: Dbs Analysismentioning
confidence: 99%
See 2 more Smart Citations